Babesia life cycle – When phylogeny meets biology - Jalovecka, Marie; Sojka, Daniel; Ascencio, Mariano E.; Schnittger, Leonhard (Elsevier, 2019)
Although Babesia represents an important worldwide veterinary threat and an emerging risk to humans, this parasite has been poorly studied as compared to Plasmodium, its malaria-causing relative. In fact, Babesia employs highly specific survival strategies during its intraerythrocytic development and its intricate journey through the tick vector. This review introduces a substantially extended molecular phylogeny of the order Piroplasmida, challenging previous taxonomic classifications. The intriguing developmental proficiencies of Babesia are highlighted and compared with those of other haemoparasitic Apicomplexa. Molecular mechanisms associated with distinctive events in the Babesia life cycle are emphasized as potential targets for the development of Babesia-specific treatments.